Evaluation of conventional radiography versus radiovisiography for endodontic working length determination - Talaeipour AR; Shaikholeslami M.; Ramazankhani N. (Tehran University of Medical Sciences, 2001)
"nAbstract: One of the major factors in a successful root canal therapy is the determination of root length before canal preparation. Radiography has been proved to be useful in this case, but nowadays for reducing radiation, radiovisiography has been recommended. The aim of this study was comparing conventional radiography (CR) with radiovisiography (RVG) in determination of canal length. 101 anterior and posterior extracted human teeth were selected. After mounting in unolit block, K- file (Num. 15) was placed in canal with tactile sense. Working length was measured by C.R and RVG. The results were analyzed by complete, randomized block design. RVG and CR showed shorter length than actual length. But, the measured lengths did not show significant statistical differences. As a result, considering the advantages of RVG, it is recommended in determining canal length.